Efektivitas Latihan Curl-up dan Core Activation pada Pemulihan Wanita Post-partum dengan Diastasis Recti Abdominis : Case Report - Nadia Salsabiela Mumtazi Luthfiah; Mahendra Wahyu Dewangga; Vivin Sari Sukmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diastasis Recti Abdominis (DRA) is a common postpartum condition in women, characterized by separation of the rectus abdominis muscles due to a weekend linea alba. This case study aimed to evaluate the effectiveness of e combined core activation.and curl-up exercise program in reducing intra-recti distance in a postpartum patient.The subject was a spontaneous postpartum woman at 39 weeks of gestation. Initial assessment revealed intra-recti distance of 28 mm above and 17 mm below the umbilicus, exceeding normal limits. The intervention consisted of a 4-day program including curl-up and five core activation excercises : diaphragmatic breathing, abdominal drawing-in manuver, supine pelvic tilt, heel slide and knee fall out. Measurements showed no significant reducyion in intra-recti distance; however, the patient reported improved abdominal tightness and core stability. The study concludes that although measurable changes were not significant within a short evaluation period, the intervention had positive subjective effects. Longer-term assessment is recommended for more conclusive results.